2021
DOI: 10.3389/fpsyt.2021.621874
|View full text |Cite
|
Sign up to set email alerts
|

An International Survey of Health Care Services Available to Patients With Tourette Syndrome

Abstract: Objective: Tourette syndrome (TS) is a neuropsychiatric disorder that is highly associated with several comorbidities. Given the complex and multifaceted nature of TS, the condition is managed by a wide variety of practitioners in different disciplines. The goal of this study was to investigate health service delivery and care practices by clinicians who see TS patients across different geographic settings internationally.Methods: A comprehensive questionnaire was developed to assess clinical care resources fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Given the limited availability of therapists trained in delivering BT for patients with tic disorders [ 48 ], focus on dissemination and adaptation of treatment delivery has increased in recent years. New modalities have been proposed to make BT more accessible, primarily by reducing the number of therapists needed and/or reducing the need for travel.…”
Section: Resultsmentioning
confidence: 99%
“…Given the limited availability of therapists trained in delivering BT for patients with tic disorders [ 48 ], focus on dissemination and adaptation of treatment delivery has increased in recent years. New modalities have been proposed to make BT more accessible, primarily by reducing the number of therapists needed and/or reducing the need for travel.…”
Section: Resultsmentioning
confidence: 99%
“… 113 This is also reflected by an excellent review highlighting the scarcity of specialized TS clinics and dedicated experts. 114 This international group investigated health service delivery and care practices by clinicians in different geographical settings (Canada, US, Europe, and the United Kingdom). The results suggested that there is a scarcity of specialized TS clinical care in all investigated regions.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Thullen and Bonsall ( 14 ) found that disruptive mealtime behaviour, food refusal and mealtime rigidity were all independently associated with increased stress in parents of children with ASD. Mothers of children with a tic disorder may also benefit from interventions to reduce mealtime-related stress, however little support is currently available for these challenges ( 42 , 45 ). Maternal accounts indicated stress/conflict avoidance as the main overarching goal of mealtimes, which has been shown to be the most common mealtime goal in parents of children aged 1–16 years ( 46 ).…”
Section: Discussionmentioning
confidence: 99%